Comparative analysis of TR CU 021 and international food safety standards in the agricultural export industry - Iskulova Dilnaz (Modern Scientific Technology, 2024)
This study investigates the comparative analysis of technical regulation and international food safety standards, focusing specifically on ISO 22000 and TR CU 021, in relation to the agricultural sector in Kazakhstan. It examines the benefits and drawbacks of implementing ISO 22000, providing insights into its effectiveness for enhancing food safety management systems. Additionally, the research presents a comparative assessment of these standards, emphasizing their implications for the exportation of agricultural products, including milk, meat, and eggs. By analyzing relevant export statistics, the study illustrates the relationship between food safety practices and international trade dynamics. The results show that by introducing international best practices and improving the regulatory framework, Kazakhstan can strengthen the export potential of agriculture, thereby contributing to economic growth and development. This study is a fundamental step towards developing strategic proposals for policy makers and industry stakeholders aimed at improving food safety standards and promoting sustainable agricultural practices in Kazakhstan.